Kualitas Even, Kepuasan Pengunjung, dan Intensi Berperilaku Pengunjung: Suatu Studi Empiris - Alexander Joseph Ibnu Wibowo (Universitas Kristen Maranatha, 2014)
Abstract: This study aims to examine the relationship between event quality (includes diversity and sponsor balance), visitor satisfaction, and behavioral intention of the visitors. Structured questionnaire was designed to collect survey data. Multiple linear regression analysis was used to test the significance of the causal relationships proposed in the hypothesis. The results showed that the diversity and sponsor balance affect visitor satisfaction. Similarly, diversity and visitor satisfaction affect the behavioral intention. However, the study also foundthat there was no influence of the sponsor balance to the behavioral intention. This study provides empirical contribution through conceptualization, and then verify empirically on a model. Empirical contribution comes from finding the strength and magnitude of the association relationship found. In addition, this study also provides practical contribution, particularly for event managers, to increase the number ofvisitors. The value of this study is centered on conceptual and empirical contributions related to the relationship between the event quality (diversity and sponsor balance), visitor satisfaction, and behavioral intention of the visitors.Keywords: Event Quality, Event Management, Visitor Satisfaction, BehavioralIntention